Holistic care of complicated tuberculosis in healthcare settings with limited resources. Issue 12 (14th September 2017) - Duke, Trevor; Kasa Tom, Sharon; Poka, Harry; Welch, Henry
Abstract : In recent years, most of the focus on improving the quality of paediatric care in low-income countries has been on improving primary care using the Integrated Management of Childhood Illness, and improving triage and emergency treatment in hospitals aimed at reducing deaths in the first 24 hours. There has been little attention paid to improving the quality of care for children with chronic or complex diseases. Children with complicated forms of tuberculosis (TB), including central nervous system and chronic pulmonary TB, provide examples of acute and chronic multisystem paediatric illnesses that commonly present to district-level and second-level referral hospitals in low-income countries. The care of these children requires a holistic clinical and continuous quality improvement approach. This includes timely decisions on the commencement of treatment often when diagnoses are not certain, identification and management of acute respiratory, neurological and nutritional complications, identification and treatment of comorbidities, supportive care, systematic monitoring of treatment and progress, rehabilitation, psychological support, ensuring adherence, and safe transition to community care. New diagnostics and imaging can assist this, but meticulous attention to clinical detail at the bedside and having a clear plan for all aspects of care that is communicated well to staff and families are essential for good outcomes. The care is multidimensional: biomedical, rehabilitative, social and economic, and multidisciplinary: medical, nursing and allied health. In the era of the Sustainable Development Goals, approaches to these dimensions of healthcare are needed within the reach of the poorest people who access district hospitals in low-income countries.